Quantification and modelling of the in vivo dose-effect relationship of antienterococcal drug combinations (2023)
ABSTRACT: Severe and multidrug-resistant enterococcal infections require bactericidal antibiotic treatment to reach optimal cure rates. Currently, there are few bactericidal antibiotics against enterococci, in consequence, combined therapies are commonly used in many clinical cases to improve efficacy by synergism. However, demonstrating the in vivo effect of the antimicrobial combinations could be challenging due to the lack of robust, validated models that evaluate the synergism, antagonism, or potentiation resulting from the drug combination. The main objective of this thesis was to determine the dose-response relationship of different antibiotics alone or combined against vancomycin-susceptible and -resistant strains of two different species of Enterococcus using an optimized and validated mouse thigh infection model. Additionally, a novel framework for quantifying the antimicrobial interactions was developed based on the sigmoid Emax model, also known as the Hill equation, which distinguishes between the following types of in vivo combined effects: (i) synergism, meaning a >2 log10 increase in the maximal efficacy (Emax) due to the drug combination; (ii) potentiation, at least 50% improvement in the potency of any of the antibiotics tested; (iii) antagonism, a >1 log10 reduction of the maximal efficacy, and (iv) indifference, when there are no significant changes in efficacy or potency.